Implementation of Go Public in the Development Indonesian Company Law (Case of PT. Astra International) - Laniati, Ratna; Rahayu, Sang Ayu Putu; Daren, Bastian Chris (Faculty of Law, Universitas Negeri Semarang, 2023)
In the competitive business landscape of Indonesia, companies vie for prominence within their respective sectors. The capital market emerges as a pivotal avenue for enterprises to secure financial resources crucial for sustaining and expanding their operations.